Feeding activity and body condition of Mute Swans Cygnus olor in rural and urban areas of a lowland river system - Sears, Jane (Wildfowl, 1989)
The winter feeding activity of five flocks of predominantly immature, non-breeding Mute Swans was monitored during 1983-84. Four different habitats within the lowland river system of the Thames valley were compared. Total body weight and muscle and fat reserves of swans from rural and urban areas were measured in order to assess whether contrasting diets and feeding rates result in variation in body condition. Swans feeding on fields of winter wheat and ley grass spent on average 67% of the time actively grazing. Those on the lake fed for 46% of the time on a diet comprised mainly of mixed filamentous green algae. In areas where members of the public fed bread to the swans, the average percentage time spent feeding was considerably reduced. The flock on the gravel pit was observed feeding for only 20% of the time and on the urban river, for 22% of the time. Bread appeared to be the preferred food. There was active competition between the swans whenever it was supplied, and relatively little natural food was eaten, even when there was no bread available. It is suggested that swans may be selecting bread due to its high digestibility. The difference in feeding activity rates between flocks in rural and urban areas was consistent throughout the year. From January to August 1984 on average 36% of the rural flock were feeding during scan observations, compared with only 14% of the urban flock. The feeding rates of the urban swans are extremely low, especially when compared with other studies. Despite the contrast between both the diet and the feeding rates of swans in urban and rural flocks, there was no significant difference in their average fat scores. Swans in the urban flock had significantly smaller breast muscle reserves but this difference may not be due to diet alone. Swans' dependence on humans for food can indirectly cause them harm; for example, their habit of begging from people draws them into areas with the highest densities of discarded lead weights, and thus increase their chances of becoming poisoned.